Study about Homocysteine: A Biomarker in Neurodegenerative Diseases - N. Jayanthi Bai; S. Jayakrishnan (Issues and Development in Health Research Vol. 7, 2021)
Indians have higher homocysteine (Hcy) levels than westerners. Hyperhomocysteinemia (HHcy) is a distinct, strong, graded, and easily quantifiable early risk factor for stroke, MI, and other vascular diseases. It could be caused by a vitamin deficiency or a hereditary abnormality. The majority of vegetarian Indians have low amounts of Vitamin B12, Vitamin B6, and folic acid, all of which are necessary for methionine metabolism. Epidemiological studies have discovered a dose-dependent link between modest to moderate increases in plasma Hcy and the risk of neurodegenerative disorders. Hcy is a neurotoxic agent that acts as a surrogate marker for vitamin deficiency. Very high Hcy concentration in patients leads to high incidence of atherosclerotic events. Hyperhomocysteinemia is a prevalent condition among the elderly. Hcy levels are higher in patients with neurologic disorders, according to the findings of this study. Hcy levels are statistically significant in both male and female individuals. Male individuals with neurological diseases have greater Hcy levels. In hyperhomocystemic high-risk patients, the availability of vitamin-fortified foods, particularly cereals, will help to prevent or delay the onset of age-related neurological problems.